2011
DOI: 10.1007/s00547-004-1023-9
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy with rescue aspiration catheter and distal protection with EPI filterwire in primary angioplasty for acute myocardial infarction

Abstract: AMI (Acute Myocardial Infarction) is usually caused by abrupt plague rupture followed by thrombus formation inside the coronary artery. Primary angioplasty for heavy thrombus loaded vessels may be complicated by distal embolization, leading to no reflow and myocardial damage. We present a case of acute thrombotic occlusion of the left anterior descending artery (LAD), in which we performed simultaneous thrombus removal by the rescue aspiration thrombectomy catheter together with an EPI FilterWire for distal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They include a distal tip with either a single central lumen (2,5) or a combination of central and side holes (6). Different solutions, mainly based on different distal tip shapes, have been suggested (2,7,8), but their effectiveness has not been really demonstrated. A number of clinical trials (5,6,9) and in vitro tests (10,11) are reported in the literature.…”
mentioning
confidence: 99%
“…They include a distal tip with either a single central lumen (2,5) or a combination of central and side holes (6). Different solutions, mainly based on different distal tip shapes, have been suggested (2,7,8), but their effectiveness has not been really demonstrated. A number of clinical trials (5,6,9) and in vitro tests (10,11) are reported in the literature.…”
mentioning
confidence: 99%